Investigation of a new lead-free (1-x-y)BNT-xBKT-yBZT piezoelectric ceramics - Sumang R. (2017)
© 2017 Elsevier Ltd and Techna Group S.r.l. Lead-free solid solutions (1-x-y)Bi 0.5 Na 0.5 TiO 3 –xBi 0.5 K 0.5 TiO 3 –yBaZr 0.05 Ti 0.95 O 3 (0≤y≤0.25 and 0.10≤x≤0.30) were prepared by using a solid-state reaction method. The effect of y(BZT) and x(BKT) contents on phase, microstructure, and electrical properties was investigated. The XRD and Raman spectra exhibited co-existing rhombohedral and tetragonal phases throughout the entire compositional range with the tetragonal phase becoming dominant at higher y(BZT) and x(BKT) concentrations. While an increased in y(BZT) content promotes grain growth, the addition of x(BKT) suppresses it. The diffuseness exponent (γ) of ceramics increased from 1.82 to 1.92 and from 0.05 to 1.77 when increased of y(BZT) and x(BKT) contents, respectively, which showed the diffuse phase transition behavior. The change in P-E loops of ceramics was closely related to relative stability of long-range order. The results reflected a competition between compositions induced tetragonality and disorder. It appears that small amount of x(BKT) and y(BZT) favor ergodic behavior, which is indicative of increased disorder and stable PNRs at zero field conditions. However, with increased amount of x(BKT) and y(BZT), non-ergodic behavior is re-introduced, most likely due to increased tetragonality. The results indicated that the addition y(BZT) and x(BKT) significantly enhances the field-induced strain in (1-x-y)Bi 0.5 Na 0.5 TiO 3 –xBi 0.5 K 0.5 TiO 3 –yBaZr 0.05 Ti 0.95 O 3 ceramics.